2003
DOI: 10.1023/a:1024162420449
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We examined the reactions of 17 male inpatients on a secure psychiatric unit to television news coverage of the September 11 attacks. All had psychotic diagnoses. We hypothesized that self-exposure and affective response to the news coverage and use of social support would be influenced by predominance of negative symptoms. Additionally, we examined for the emergence of common stress symptoms and exacerbations of psychosis. Results showed a dose-response relationship between amount of viewing and magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…31 A few studies have reported that 20–30% of psychotic patients took the September 11 attacks into their delusions. 32, 33 …”
Section: Discussionmentioning
confidence: 99%
“…31 A few studies have reported that 20–30% of psychotic patients took the September 11 attacks into their delusions. 32, 33 …”
Section: Discussionmentioning
confidence: 99%